2017
DOI: 10.1177/1468087417699753
|View full text |Cite
|
Sign up to set email alerts
|

Numerical studies of the ignition characteristics of a high-pressure gas jet in compression-ignition engines with glow plug ignition assist: Part 1—Operating condition study

Abstract: This article presents the results of computational studies investigating the ignition of high-pressure natural gas jets in a compression-ignition engine with glow plug ignition assist. The simulation was conducted using a KIVA-3V-based three-dimensional engine model, along with an improved fuel injector model, a detailed cut-off glow plug shield model and a modified two-step methane reaction mechanism, to simulate the natural gas injection and ignition. The simulated results demonstrate the significance of usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…Based on this engine configuration, a KIVA computational model was developed to represent only the geometry and structure of the CFR engine’s external combustion chamber, 38,4447 where the fuel injection and ignition occurred, as shown in Figure 2(b). The engine model has been validated by experimental data 48,49 that indicates the computational model can well simulate the jet penetration, fuel mixing, and hence ignition and flame propagation.…”
Section: Methodology—computational Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on this engine configuration, a KIVA computational model was developed to represent only the geometry and structure of the CFR engine’s external combustion chamber, 38,4447 where the fuel injection and ignition occurred, as shown in Figure 2(b). The engine model has been validated by experimental data 48,49 that indicates the computational model can well simulate the jet penetration, fuel mixing, and hence ignition and flame propagation.…”
Section: Methodology—computational Modelmentioning
confidence: 99%
“…Employing a shield can insulate the GP from the cooling flows of intake air and the subsequent injected natural gas jets. 38–43 Part 1 of this study 38 was a simulation that validated that a shielded GP can improve the ignition stability over a full range of engine operating conditions. However, the part 1 simulations also showed that flame propagation out of the shield will sometimes be delayed under several operating conditions when injecting the fuel jets onto a GP employing a shield with a single circular opening.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Catapano et al 20 experimentally optimized the injection process in an SI DI-CNG engine to reduce the coefficient of variation (CoV) of combustion and improve the power output. Pan and Wallace 21,22 studied the ignition characteristics of high-pressure gas jets in the context of compression ignition (CI) engines using a cylindrical nozzle design for the direct injector. In the very recent experimental investigations of CI DI-CNG engine, Rochussen et al 23 performed a parametric study of NG combustion in an optical heavy-duty engine.…”
Section: Introductionmentioning
confidence: 99%